Viabilidade sócio ambiental do cooperativismo no setor de pesca profissional na Baixada Cuiabana/MT - Ávila, Gabriela Rocha Priante Teles de (Universidade Federal de São Carlos, 2011)
Changes in vectors that indirectly affect biodiversity, including population, technology and lifestyle, may lead to changes in vectors that affect biodiversity directly, including fishing and fertilizer application. This result in changes in ecosystems and services they offer, affecting human well-being. These interactions can occur in more than one scale. Different strategies and interventions can be applied in many parts of this structure in order to ensure the well‐being and conserve the ecosystems. Traditional communities have their way of life related to their living environment, and recently have been studied in order to ensure sustainability with a focus on human well‐being based on the Millennium Ecosystem Assessment, in order to implement the established in the National Politics of Sustainable Development to Traditional Peoples and Communities. This study was conducted at the Fishermen Cooperative and Artisans of Pai André and Bonsucesso (Coorimbatá), which gathers people from the urban area of Cuiabá and riverine communities of Bonsucesso and Pai André, located in Várzea Grande, Mato Grosso, to assess the strategies adopted by Cooperative for the well-being of the cooperative members and the use of natural resources of local biodiversity. The study s hypothesis is that the way the Cooperative Coorimbatá was structured from the amendment of its Statute in 2000, meets the fundamentals of the Millennium Ecosystem Assessment with regard to the conservation and sustainable use of ecosystems. It also contributes to creating environments for dialogue and action for the sharing of knowledge between traditional peoples and academics, looking forward the human well-being. The method used to prove whether or not this hypothesis has the qualitative research approach to data sources in semi-structured interviews with the founders of the Cooperative Coorimbatá and fishermen from Bonsucesso and Pai André communities, projects and reports made by Coorimbatá. Within an ergological focus, were also made visits to local fishing community of Bonsucesso, with interviews by the self-confrontation method, to obtain additional information to better understand this phenomenon. The semi-structured interview was made from a questionnaire with questions regarding: life history; Cooperative Coorimbatá meaning; type of work, leaders identification, Cooperative s expectations. Initially, the Cooperative main product was fish, however due to this natural resource is no longer available as it was in previous years, the Cooperative began to add other products in its supply chain as fruits raisins (dried), cassava chips, brazilian nuts and more recently the alligator. Know and reveal the lifestyle of these members, their relationships and interactions with the river are important tools to be used in discussions and implementation of public politics.
Keywords: Ecologia; Pesca tradicional; Cooperativa; Ergologia; Sustentabilidade; Comunidades tradicionais; Pesca profissional artesanal; Artisanal fishery; Cooperative; Ergology; Sustainnability; CIENCIAS BIOLOGICAS::ECOLOGIA